A single small molecule fluorescent probe for imaging RNA distribution and detecting endogenous SO2 through distinct fluorescence channels. (12th October 2021) - Wang, Zhaomin; Liu, Yong; Wang, Weishan; Zhao, Chang; Lin, Weiying
Abstract : Herein, we developed a novel small molecule fluorescent probe for imaging the distribution of RNA and detecting endogenous SO2 through distinct fluorescence channels in cells. Abstract : Fluorescent probes are a powerful tool in biological and biochemical fields. Herein, we prepared a new small molecule fluorescent probe PYQU as a robust tool that can explore the interaction between RNA and SO2 in biological environments. The probe PYQU could detect SO2 and RNA by a change in green and red fluorescence, respectively. Besides, the probe PYQU has excellent properties, such as low biological toxicity, good membrane permeability, and high selectivity. PYQU was used to detect SO2 in living cells and zebrafish in the green channel and visualize endogenous RNA of cells with a deep red fluorescence signal. Therefore, we believe that the probe PYQU is a valuable, robust, and reliable tool for studies of RNA and SO2 .